2010
DOI: 10.1051/forest/2010047
|View full text |Cite
|
Sign up to set email alerts
|

Global pattern of leaf litter nitrogen and phosphorus in woody plants

Abstract: Abstract• Forest ecosystems exert an important influence on global biogeochemical cycles. A global dataset of nitrogen (N) and phosphorus (P) concentrations in leaf-litter of woody plants was compiled from the literature. Among the 677 data sets, 482 included P concentrations and the N:P ratio.• At a global scale, the mean leaf-litter N and P and N:P ratio were 10.9 mg g −1 , 0.85 mg g −1 and 18.3, respectively. Leaf-litter N and P were significantly correlated. When the data was grouped by continents, the hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(28 citation statements)
references
References 23 publications
0
27
1
Order By: Relevance
“…Additionally, at high elevations, litterfall rates are lower, and plants from these regions tend to be evergreen (de Sousa-Neto et al, 2017;Lu & Lui, 2012). In contrast to other studies (Kang et al, 2010;Tang, Han, Chen, & Fang, 2013;Yuan & Chen, 2009), lower latitudes were associated with complete N resorption. It may be that our data set was limited by fewer high relative to low latitude sites, precluding our ability to detect stronger trends in latitudinal variation.…”
Section: Are N and P Resorption Linked To Plant Nutrient Status Eacontrasting
confidence: 99%
“…Additionally, at high elevations, litterfall rates are lower, and plants from these regions tend to be evergreen (de Sousa-Neto et al, 2017;Lu & Lui, 2012). In contrast to other studies (Kang et al, 2010;Tang, Han, Chen, & Fang, 2013;Yuan & Chen, 2009), lower latitudes were associated with complete N resorption. It may be that our data set was limited by fewer high relative to low latitude sites, precluding our ability to detect stronger trends in latitudinal variation.…”
Section: Are N and P Resorption Linked To Plant Nutrient Status Eacontrasting
confidence: 99%
“…Wood data are shown as global, tropical, temperate/boreal, angiosperm, and gymnosperm averages, root litter data as global, broadleaf, conifer, fine-, and coarse-root averages, and leaf litter data as global, tropical, temperate, broadleaf forest, coniferous forest, and tundra averages. Data were from the following sources: C:N:P stoichiometry (Harmon et al 1986, Aerts 1997a, Martinelli et al 2000, Silver and Miya 2001, Zhang et al 2008, Yuan and Chen 2009, Kang et al 2010, Yuan et al 2011; decomposition (Harmon et al 1986, Aerts 1997a, Silver and Miya 2001, Zhang et al 2008, van Geffen et al 2010). N and P (increasing C limitation).…”
Section: Mechanisms Regulating Microbial Carbon and Nutrient Cycling mentioning
confidence: 99%
“…Reich & Oleksyn, 2004;Sardans et al, 2013) and its resorption in trees (e.g. Indeed, global patterns of leaf litter nutrient variation at regional (Aerts, 1997;Liu et al, 2006) and global scales (Aerts, 1997;Kang et al, 2010;McGroddy et al, 2004;Yuan & Chen, 2009b) have been identified. Therefore, leaf litter nutrients are expected to be partially climate dependent.…”
Section: Leaf Litter Elemental Composition: a Proxy Of Ecosystem Numentioning
confidence: 99%